Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20174289
|View full text |Cite
|
Sign up to set email alerts
|

Lysates of a Probiotic, Lactobacillus rhamnosus, Can Improve Skin Barrier Function in a Reconstructed Human Epidermis Model

Abstract: The main function of the skin is to protect the body from the external environment. The barrier function of the skin is mainly provided by the stratum corneum, which consists of corneocytes bound with the corneodesmosomes and lamellar lipids. Skin barrier proteins like loricrin and filaggrin also contribute to the skin barrier function. In various skin diseases, skin barrier dysfunction is a common symptom, and skin irritants like detergents or surfactants could also perturb skin barrier function. Many efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 33 publications
2
42
0
3
Order By: Relevance
“…Although live LAB, thanks to their active metabolism, have the advantage to produce potent antimicrobials (e.g., bacteriocins, organic acids, hydrogen peroxide) that could prevent adhesion and growth of some skin pathogens, they are generally not preferred in topical application, especially in situations where the skin barrier is breached 8 , 13 . In a wound situation, the potential risks of live LAB entering the bloodstream through breached skin have not been assessed, thus it is usually preferred to exploit the immunostimulating and anti-inflammatory power of lysates by giving up to antibacterial properties of live LAB 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although live LAB, thanks to their active metabolism, have the advantage to produce potent antimicrobials (e.g., bacteriocins, organic acids, hydrogen peroxide) that could prevent adhesion and growth of some skin pathogens, they are generally not preferred in topical application, especially in situations where the skin barrier is breached 8 , 13 . In a wound situation, the potential risks of live LAB entering the bloodstream through breached skin have not been assessed, thus it is usually preferred to exploit the immunostimulating and anti-inflammatory power of lysates by giving up to antibacterial properties of live LAB 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lactobacillus rhamnosus GG lysate accelerates re-epithelialization of keratinocyte monolayers by increasing the expression of CXCL2 chemokine and of its receptor, CXCR2, that induce the keratinocyte migration 7 . Very recently, it has been also showed that Lactobacillus rhamnosus LR lysate improves skin barrier function in a reconstructed human epidermis model 8 , and that a multi-strain probiotic formulation, used as a topical treatment, improve the healing of infected chronic ischemic wound lesion 9 . Moreover, Lactobacillus reuteri ATCC-55730 exerts an anti-inflammatory effect on infected keratinocytes by reducing their transcription level of interleukin (IL)-8 and human-beta-defensin (hBD)-2 10 ; while Lactobacillus plantarum K8 inhibits tumor necrosis factor-alpha (TNF-α) or interferon-gamma (IFN-γ) expression in keratinocytes through the lipoteichoic acid that is contained in its cell wall 11 .…”
Section: Introductionmentioning
confidence: 99%
“…L. bulgaricus, also in this context, did show no effect. IL-6 and IL-8 are reported to be involved in the phosphatidylinositol 3 kinase (PI3K)/protein kinase B (Akt) pathway [52]; interestingly Lactobacillus rhamnosus and Lactobacillus reuteri lysates promoted wound healing process via the PI3K/Akt pathway in a reconstructed human epidermis model and gingiva mesenchymal stem cells, respectively [53,54]. Based on these observations, the involvement of the PI3K/Akt pathway in the acceleration of the in vitro wound healing process stimulated by S. thermophilus, L. plantarum, and L. acidophilus samples could be also examined.…”
Section: Discussionmentioning
confidence: 99%
“…Rhodamine B, a hydrophilic dye, was applied to evaluate the permeability of the skin as described previously [ 41 ]. Treated tissues were incubated for 24 h and rinsed with PBS.…”
Section: Methodsmentioning
confidence: 99%